POLITIK IDENTITAS AGAMA LOKAL (Studi Kasus Aliran Kebatinan) - Hakiki, Kiki Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2011)
Even though experiencing much discrimination in this country, the existence of local religion such as mysticism stream steadily grows and even still attracts many followers. Truth claim that is frequently voiced by formal religions such as Islam, Catholic, Christian, Buddha, Hindu and Confucius is not frightening to adherents of local religion, even less converting to another belief. Interestingly, the adherents’ belief of formal religion whether aware or not often has mixed with the belief of local religion